Working as a Therapist while Suffering War in Ukraine - Marharyta Chaika (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas)
The article highlights the personal experiences of a therapist who is an internally displaced person from a hot spot in the war in Ukraine. The therapist shares her personal experience on how to stabilize her own psycho-emotional state, how to fix the lost connection between the psyche and the body, how to return to the usual way of life after an evacuation, and how to continue the work of the therapist. In the same period, she developed Alternative and Augmentative Communication (AAC) visual materials to support people with developmental disabilities in understanding and dealing with evacuation and being at war. This article provides examples of emotional stabilization, on the level of the client, and how AAC posters that focus on war can help stabilize the psychological state of clients with a mental disability. At the level of the therapist, it shows the experience of the author in organizing her work as a therapist in a war situation. The AAC materials can be useful both in war conditions and in other emergencies or natural disasters. The described case may help other therapists to understand in more detail how clients experience the situation of war and evacuation using the experience of Ukrainians as an example.